Age differences in vocal emotion perception: on the role of speaker age and listener sex. Issue 6 (18th August 2018) - Sen, Antarika; Isaacowitz, Derek; Schirmer, Annett
ABSTRACT: Older adults have greater difficulty than younger adults perceiving vocal emotions. To better characterise this effect, we explored its relation to age differences in sensory, cognitive and emotional functioning. Additionally, we examined the role of speaker age and listener sex. Participants ( N  = 163) aged 19–34 years and 60–85 years categorised neutral sentences spoken by ten younger and ten older speakers with a happy, neutral, sad, or angry voice. Acoustic analyses indicated that expressions from younger and older speakers denoted the intended emotion with similar accuracy. As expected, younger participants outperformed older participants and this effect was statistically mediated by an age-related decline in both optimism and working-memory. Additionally, age differences in emotion perception were larger for younger as compared to older speakers and a better perception of younger as compared to older speakers was greater in younger as compared to older participants. Last, a female perception benefit was less pervasive in the older than the younger group. Together, these findings suggest that the role of age for emotion perception is multi-faceted. It is linked to emotional and cognitive change, to processing biases that benefit young and own-age expressions, and to the different aptitudes of women and men.